Chalkboards to Virtual Environments: Technology's Role in Expanding the Classroom to Provide Professional Development and Education for Agricultural Communicators - Theresa Pesl Murphrey; Tracy A. Rutherford; David. L. Doerfert; Leslie D. Edgar; Don W. Edgar; Holli Leggette (Journal of Applied Communications, 2013)
Agricultural communications education has evolved over time, shifting in an effort to meet the needs of students through new approaches, new methods, and new technologies. The purpose of this paper was to examine the influence of educational and communications technologies on agricultural communications education. A literature review related to the history of the processes, methods, and technology uses in education and more specifically in agricultural communications education was conducted. Technology was identified as enhancing learning in settings that included secondary education, university settings, continuing education, Extension programming, and professional development. Only a limited number of articles specifically addressed the use of technology to teach agricultural communications. The high rate of change in communication technologies was identified as a critical reason for considering the role of technology in the agricultural communications education context. A virtual environment to teach crisis communications was shared as an example of successful educational technology use. Continued research focusing on teaching methods and tools related to agricultural communications education is needed. New technologies have the potential to encourage innovative learning experiences; however, the ongoing challenge to educators will be to harness the technology for the good of the learner.
Keywords: agricultural communications; education; technology; distance education